PROFESSIONAL DEVELOPMENT IN EDUCATION: A BIBLIOMETRIC ANALYSIS (2020-2025) - Azis, Jumriah Abdul; Dzulkifli , Dg Norizah Ag Kiflee; Ambatong, Abdul Said (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis examines global research patterns in educational professional development between 2020 and 2025, exploring publication trends, collaborative networks, and emerging themes. The study analyzed 27,808 Scopus-indexed articles using VOSviewer to visualize scholarly relationships and research directions. Key findings indicate substantial growth in PD publications, rising from 3,388 articles in 2020 to 6,748 in 2025, reflecting increasing worldwide acknowledgment of PD's critical role in enhancing teacher capabilities and driving educational reform. Most research outputs (81.2%) were published in peer-reviewed journals, underscoring their central position in scholarly communication. Analysis of keyword patterns revealed four major thematic areas: instructional practices, psychology in education, research approaches, and professional identity formation. Common keywords such as "professional development," "teaching," and "qualitative research" demonstrate the field's cross-disciplinary character. Examination of co-authorship patterns showed concentrated collaboration among specific scholars, notably Czapla Michał and Karniej Piotr. At the international level, China, the United States, and the United Kingdom led contributions, with robust collaborative networks extending across European and Asia-Pacific regions. The research concludes that PD scholarship continues its expansion, fueled by digital transformation, post-pandemic educational changes, and evolving policies. Nevertheless, significant gaps persist in developing nations where PD resources remain limited, highlighting the necessity for inclusive, culturally appropriate, and digitally supported approaches to guarantee equitable professional growth opportunities globally.